Brettanomyces bruxellencis: μέθοδοι ανίχνευσης του κατά την περίοδο παλαίωσης ερυθρών οίνων - Ευαγγέλου, Χάρης (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
Brettanomyces bruxellencis is an indigenous yeast that grow during wine fermentation and maturation in oak barrels. The yeast has been isolated from grapes, barrels and winery equipment. That yeast is the biggest example of Custer effect. Brettanomyces bruxellensis is a major threat to wine industry due to its spoilage ability characterized by high production of volatile phenols. The horse sweat odor, medicinal, burnt plastic are the main characteristics of their volatile products. The yeast causes large economic losses to wineries worldwide. It is believed that is one of the most important microbiological challenge of modern winemaking. In the present work, we studied the cultivation of samples of red wine that maturated in oak barrels in specific nutrition media through 3 different methods. Secondly, polymerase chain reaction (PCR) was used to identify the suspected colonies. Furthermore, a flow chart will be made for the time and process of the most efficient method. Finally, an attempt to link the positive samples with factors such as the number of times the barrel was filled with a new batch, and the practical methods used to decontaminate it.
Keywords: Brettanomyces bruxellencis; Red wines; Culturing; PCR; Hygiene; Brettanomyces bruxellencis; Ερυθροί οίνοι; Καλλιέργεια; PCR; Υγιεινή